Neurodiversity Inclusive Early Childhood Education for Generation Alpha and Generation Beta: A Review - Emmanuel Lucas Nwachukwu; Sule Omeiza Adebayo; Regina Ijeoma Ukwuoma (Asian Journal of Early Childhood and Elementary Education, 2026)
Early childhood classrooms increasingly serve children growing up under conditions of pervasive digital exposure and an evolving understanding of neurological variation as a natural dimension of human development rather than solely as a deficit requiring remediation. This narrative review examines how early childhood education systems can adapt to support neurodivergent learners within the generational contexts of Generation Alpha (born 2010–2024) and the emerging Generation Beta (born from 2025). Literature was identified from Scopus, Web of Science, ERIC, and Google Scholar, encompassing peer-reviewed articles, books, and reports published between 2018 and 2026. Searches combined terms related to neurodiversity, early childhood education, Generation Alpha, Generation Beta, Universal Design for Learning, assistive technology, and multi-tiered systems of support. Sources were included when they addressed neurodevelopmental variation, inclusive pedagogy, or generational characteristics relevant to early childhood or closely related educational settings. The review synthesizes the developmental and technological characteristics of Generation Alpha alongside the emerging profile of Generation Beta and examines Universal Design for Learning and artificial intelligence-supported assistive technologies as pedagogical approaches for neurodivergent learners. It further identifies teacher preparedness and multi-tiered systems of support as essential mechanisms for addressing persistent inequities in early childhood classrooms. The review concludes that meaningful inclusion for neurodivergent children cannot be achieved through a single intervention but requires a coordinated educational architecture integrating teacher preparation, inclusive physical and digital learning environments, assistive technologies, and tiered support systems. This review contributes a generationally responsive perspective to inclusive early childhood education by emphasizing the need for coherent and continuous support structures that accompany neurodivergent learners from infancy through the transition into formal schooling.